Tumor suppressive microRNA-218 inhibits cancer cell migration and invasion by targeting focal adhesion pathways in cervical squamous cell carcinoma - YAMAMOTO, NORIKO (D.A. Spandidos, 2013)
Cervical cancer is one of the most common cancers in women. More than 275,100 women die from cervical cancer each year. Cervical squamous cell carcinoma (cervical SCC), one of the most frequent types of cervical cancers, is associated with high-risk human papilloma virus (HPV), although HPV infection alone may not be enough to induce malignant transformation. MicroRNAs (miRNAs), a class of small non-coding RNAs, regulate protein-coding gene expression by repressing translation or cleaving RNA transcripts in a sequence-specific manner. A growing body of evidence suggests that miRNAs contribute to cervical SCC progression, development and metastasis. miRNA expression signatures in SCC (hypopharyngeal SCC and esophageal SCC) revealed that miR-218 expression was significantly reduced in cancer tissues compared with adjacent non-cancerous epithelium, suggesting that miR-218 is a candidate tumor suppressor. The aim of this study was to investigate the functional significance of miR-218 in cervical SCC and to identify novel miR-218-mediated cancer pathways in cervical SCC. Restoration of miR-218 significantly inhibited cancer cell migration and invasion in both HPV-positive and HPV-negative cervical SCC cell lines. These data indicated that miR-218 acts as a tumor suppressor in cervical SCC. Our in silico analysis showed that miR-218 appeared to be an important modulator of tumor cell processes through suppression of many targets, particularly those involved in focal adhesion signaling pathways. Gene expression data indicated that LAMB3, a laminin protein known to influence cell differentiation, migration, adhesion, proliferation and survival, was upregulated in cervical SCC clinical specimens, and silencing studies demonstrated that LAMB3 functioned as an oncogene in cervical SCC. The identification of novel tumor-suppressive miR-218-mediated molecular pathways has provided new insights into cervical SCC oncogenesis and metastasis.